Epidendrum fimbriatum - Karremans Lok, Adam Philip (2018)
Epidendrum fimbriatum is recognized by its terrestrial or lithophytic habit, scandent stems, distichous leaves, an apical inforescence of numerous and successive non resupinate fowers. The tiny flowers are snow white spotted with purple and a fimbriate lip. It is widely distributed in the three cordilleras of the Andes in Colombia at high elevations where it can be found in large masses along roadsides.